Does task complexity impact the neurovascular coupling response similarly between males and females?. Issue 17 (13th September 2021) - Burma, Joel S.; Wassmuth, Rebecca M.; Kennedy, Courtney M.; Miutz, Lauren N.; Newel, Kailey T.; Carere, Joseph; Smirl, Jonathan D.
Abstract: Background: While previous studies have demonstrated a complex visual scene search elicits a robust neurovascular coupling (NVC) response, it is unknown how the duration of visual stimuli presentation influences NVC metrics. This study examined how stimuli duration, in addition to biological sex and self‐reported engagement impact NVC responses. Methods: Participants (n = 20, female = 10) completed four visual paradigms. Three involved simple visual shapes presented at 0.5‐, 2‐, and 4‐s intervals in randomized orders. The fourth paradigm was a complex visual scene search (" Where's Waldo? "). Participants completed eight cycles of 20‐s eyes‐closed followed by 40‐s eyes‐open. Transcranial Doppler ultrasound indexed posterior and middle cerebral artery velocities (PCA and MCA). Participants self‐reported their engagement following each task (1 [minimal] to 10 [maximal]). Results: The " Where's Waldo? " task evoked greater PCA percent increase (all p  < 0.001) and area under the curve during the first 30‐s of the task (all p  < 0.001) compared to simple shapes. Females displayed greater absolute baseline and peak PCA and MCA velocities across all tasks (all p  < 0.002). Subjective engagement displayed moderate correlation levels with PCA percent increase (Spearman ρ  = 0.58) and area under the curve (Spearman ρ  = 0.60) metrics in males, whereas these were weak for females (Spearman ρ  = 0.43 and ρ  = 0.38, respectively). Conclusions: The complex visual paradigm " Where's Waldo? " greatly augmented the signal‐to‐noise ratio within the PCA aspects of the NVC response compared to simple shapes. While both sexes had similar NVC responses, task engagement was more related to NVC metrics in males compared to females. Therefore, future NVC investigations should consider task engagement when designing studies. Abstract : A simple shapes task elicited a modest neurovascular coupling (NVC) response, regardless of image presentation duration (4‐, 2‐, or 0.5‐s). Conversely, a complex "Where's Waldo?" search produced a robust response that maximized the NVC response. While absolute cerebral blood velocity metrics were higher in females, no differences were found between biological sexes regarding the NVC response. However, subjective task engagement had a greater correlation within males, highlighting the need for researchers to use more engaging tasks for males to elicit a similar NVC response compared to females.